Variasi morfologi puparium Bemisa tabaci (Gennadius) (Hemiptera: Aleyrodidae) pada berbagai inang dan ketinggian tempat dari daerah endemik penyakit kuning cabai di Wilayah Sundaland - Sat Rahayuwati; Purnama Hidayat; Sri Hendrastuti Hidayat (Jurnal Entomologi Indonesia, 2020)
Bemisia tabaci (Gennadius) is one of polyphagous whitefly that has been known as gemini virus vector. The identification of B. tabaci is carried out based on pupal case or puparium of red eye fouth stage. The morphological variation of B. tabaci puparium leads to the difficulties on species identification. This research was aimed to study the morphological variations of B. tabaci puparium that has been found in various host plants at various altitude. Samples of B. tabaci puparium were obtained from Sundaland endemic area of pepper yellow curl disease virus endemic areas including West Sumatra, West Java, Central Java, East Java, Bali, South Kalimantan. Slides-mounted were made from puparium and then identification was carried out to species. Observations have been conducted on B. tabaci puparial size, puparial shape, number of elongated dorsal setae, and caudal setae size. Canonical correlation analysis was applied to determine the factors that affected the puparium morphological variation. Based on the results, there were four variations of puparium: oval, oval with 1–2 indentations, oval with more than 3 indentations, and sea shell shapes. The variation observed on dorsal setae number, puparial shape, and size of B. tabaci were supposed due to the induction of trichomes on the leaves surface. Puparium variations were affected by host plants instead of altitude.